Influence of the physic-methodological model on the deaf youth (2020)
The objective of this article was to evaluate the influence of the physics and urban, methodological model on the development of physical-mathematical thinking in deaf students based on research in context. Through a scale of 20 items applied to a population of 120 young deaf people between 15 and 18 years old. Factor analysis showed dimensions of pedagogical practice oriented and associate with physic thinking, variational, logical reasoning and axiomatic structure, emotional satisfaction, creative attitude, productivity, leadership competencies, motivation; internal consistency of the instrument was adequate (Cronbach alpha 0.81-0.95), a global intraclass correlation coefficient of 0.97 (95%), average differences in sum of items -1.1 (standard deviation 5.5). Physics and Urban influenced the development of physical-mathematical thinking in deaf youth in the context of "San José de Cúcuta, Colombia".